How does competition among wild type mosquitoes influence the performance of Aedes aegypti and dissemination of Wolbachia pipientis? - Suellen de Oliveira; Daniel Antunes Maciel Villela; Fernando Braga Stehling Dias; Luciano Andrade Moreira; Rafael Maciel de Freitas (Public Library of Science (PLoS), 2017)
Wolbachia has been deployed in several countries to reduce transmission of dengue, Zika and chikungunya viruses. During releases, Wolbachia-infected females are likely to lay their eggs in local available breeding sites, which might already be colonized by local Aedes sp. mosquitoes. Therefore, there is an urgent need to estimate the deleterious effects of intra and interspecific larval competition on mosquito life history traits, especially on the duration of larval development time, larval mortality and adult size.Three different mosquito populations were used: Ae. aegypti infected with Wolbachia (wMelBr strain), wild Ae. aegypti and wild Ae. albopictus. A total of 21 treatments explored intra and interspecific larval competition with varying larval densities, species proportions and food levels. Each treatment had eight replicates with two distinct food levels: 0.25 or 0.50 g of Chitosan and fallen avocado leaves. Overall, overcrowding reduced fitness correlates of the three populations. Ae. albopictus larvae presented lower larval mortality, shorter development time to adult and smaller wing sizes than Ae. aegypti. The presence of Wolbachia had a slight positive effect on larval biology, since infected individuals had higher survivorship than uninfected Ae. aegypti larvae.In all treatments, Ae. albopictus outperformed both wild Ae. aegypti and the Wolbachia-infected group in larval competition, irrespective of larval density and the amount of food resources. The major force that can slow down Wolbachia invasion is the population density of wild mosquitoes. Given that Ae. aegypti currently dominates in Rio, in comparison with Ae. albopictus frequency, additional attention must be given to the population density of Ae. aegypti during releases to increase the likelihood of Wolbachia invasion.